2018
DOI: 10.1159/000487287
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MicroRNA-448 and SIRT1 and Prognosis of Obese Type 2 Diabetic Mellitus Patients After Laparoscopic Bariatric Surgery

Abstract: Background/Aims: This study sought to investigate the expression and prognostic value of peripheral blood microRNA-448 (miR-448) and its target gene SIRT1 after laparoscopic bariatric surgery in obese type 2 diabetic mellitus (T2DM) patients. Methods: Obese T2DM patients were selected and treated with laparoscopic bariatric surgery. Enzyme-linked immunosorbent assay (ELISA) was used to measure SIRT1 protein expression. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was employed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…[34,35] MiR-448 was recently found to reduce in peripheral blood of T2D patients after laparoscopic bariatric surgery and overexpressed miR-448 suppressed the viability and invasion of circulating endothelial progenitor cells through targeting SIRT1. [36] In contrast to TLR4, our data showed that miR-448 was significantly decreased in T2D mice-derived macrophages. More importantly, miR-448 was identified as the potential miRNA interacting with TLR4 3 0 -UTR by bioinformatics predictions, and this forecast result was demonstrated by our data of dual-luciferase gene reporter assay.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…[34,35] MiR-448 was recently found to reduce in peripheral blood of T2D patients after laparoscopic bariatric surgery and overexpressed miR-448 suppressed the viability and invasion of circulating endothelial progenitor cells through targeting SIRT1. [36] In contrast to TLR4, our data showed that miR-448 was significantly decreased in T2D mice-derived macrophages. More importantly, miR-448 was identified as the potential miRNA interacting with TLR4 3 0 -UTR by bioinformatics predictions, and this forecast result was demonstrated by our data of dual-luciferase gene reporter assay.…”
Section: Discussionmentioning
confidence: 56%
“…As small, non‐protein coding RNA, miR‐448 played an essential role in cellular functions, including proliferation, migration, and apoptosis through regulating the expression of targeted mRNAs . MiR‐448 was recently found to reduce in peripheral blood of T2D patients after laparoscopic bariatric surgery and overexpressed miR‐448 suppressed the viability and invasion of circulating endothelial progenitor cells through targeting SIRT1 . In contrast to TLR4, our data showed that miR‐448 was significantly decreased in T2D mice‐derived macrophages.…”
Section: Discussionmentioning
confidence: 62%
“…Only one very recent study focused on epigenomics and bariatric surgery efficacy. Even though it should be verified in an independent study, this work suggests that miR-448 and its target gene SIRT1 could serve as prognostic indicators for obese T2D patients after laparoscopic bariatric surgery (114). That study was performed using peripheral blood obtained from obese T2D patients.…”
Section: Possible Therapeutic Direction In the Futurementioning
confidence: 90%
“…Particularly, miR-138 was demonstrated to suppress NSCLC cell growth, metastasis and autophagy via targeting SIRT1 (24). Although a previous study investigated miR-448 and SIRT1 in patients with diabetes mellitus (30), their role in cancer cells, particularly NSCLC cells, remains unknown. In clinical samples, the expression of SIRT1 was higher in tumor tissues and its levels were inversely correlated with miR-448 levels.…”
Section: Discussionmentioning
confidence: 99%